Mapping the Publication Trends of the Journal of Big Data through Bibliometric Perspectives - KUMAR, AMIT; Deka, Manashjyoti; Komut, Janu (Qualitative and Quantitative Methods in Libraries, 2022)
The study examines papers published in the Journal of Big Data between 2016 and 2020. Over the period, 352 articles were published in the journal. The study includes findings of year-wise distributions of articles, growth rates of publications, authors, etc. The most contributions were made in 2019 with 113, and the least was in 2016 with 26. Among 54 different countries around the world, the USA scores in 1st rank. And further, the majority of articles were contributed by three authors, with 108 articles, followed by two authors with 105 articles. Taghi M. Khoshgoftaar is the most prolific author followed by Justin Zhan and Joffrey L. Leevy. A total of 1102 authors contributed 352 articles with average productivity of 3.13%.